The electoral consequences of corruption scandals in Spain - Riera, Pedro (Crime, law and social change, 2013)
Previous studies of the electoral consequences of corruption in Spanish local elections (Jiménez Revista de Investigaciones Políticas y Sociológicas, 6(2):43-76, 2007; Fernández-Vázquez and Rivero 2011, Consecuencias electorales de la corrupción, 2003-2007. Estudios de Progreso, Fundación Alternativas; Costas et al. European Journal of Political Economy: 28(4):469-484, 2012) have found that voters do not necessarily punish corrupt mayors. As has been pointed out in the comparative literature, the average loss of electoral support by corrupt incumbents is small and does not prevent their reelection most of the times (Jiménez and Caínzos 2006, How far and why do corruption scandals cost votes? In Garrard, J. and Newell, J. (eds.) Scandals in past and contemporary politics. Manchester: Manchester University Press). What remains unsolved, however, is the remarkable variability in this pattern. This article explores some of the micro-level variables that may mediate the effect of corruption scandal on the votes. We focus on three factors: ideological closeness to the incumbent party, political sophistication, and employment status. Our results provide only partial support for our hypotheses, suggesting that the effects of corruption are much more complex than what may seem at first sight.